2019
DOI: 10.1108/ijpdlm-06-2018-0223
|View full text |Cite
|
Sign up to set email alerts
|

The impact of product variety on LSQ in e-marketplaces

Abstract: Purpose The purpose of this paper is to reveal the impact of the e-tailers’ product variety decisions on their logistics service quality (LSQ) in B2C e-marketplaces. Furthermore, it investigates the mediation of transaction intensity and the moderation of the perceived technical quality in this relationship. Design/methodology/approach The data were collected from one of Turkey’s biggest e-marketplace firms, N11.com. Consumer evaluations and the e-tailers’ product offers were used to operationalize research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 71 publications
(94 reference statements)
0
7
0
3
Order By: Relevance
“…Murfield et al (2017) identified LSQ components in the OC context as timeliness, availability and condition. However, easiness of return must also be considered as another important dimension of the LSQ in online sales since the possibility of returning a product is much higher in online sales than in physical sales; this is due to the customer's inability of physically inspecting and trying on products before purchase (Sorkun, 2019).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Murfield et al (2017) identified LSQ components in the OC context as timeliness, availability and condition. However, easiness of return must also be considered as another important dimension of the LSQ in online sales since the possibility of returning a product is much higher in online sales than in physical sales; this is due to the customer's inability of physically inspecting and trying on products before purchase (Sorkun, 2019).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Sellers must provide product heterogeneity to consumers (Um, Lyons, Lam, Cheng and Dominguez-Pery, 2017) since it offers decision flexibility, giving them freedom of choice (Amanah and Harahap, 2018). Sorkun (2019) stated that online stores could offer various products due to the virtually unlimited shelf space. Consequently, increasing product variety create extensive inventory levels, enhancing competitiveness and sales within the online marketplace (Wan and Sanders, 2017).…”
Section: Product Varietymentioning
confidence: 99%
“…Gandhi et al (2018b) relacionam-se pois são trabalhos que envolvem a elaboração e aplicação de um modelo de avaliação da qualidade de serviço promovidas pelos funcionários. Dentre os artigos selecionados no portfólio final, destacou-se a presença dos grupos de tecnologia (AKMAN;DAGDEVIREN, 2018;CHEN;JAW;WU, 2016;KHAYER et al, 2020), negócios digitais (GHOBAKHLOO;HONG;STANDING, 2015;SORKUN, 2019;SURYANI;FAUZI;NURHADI, 2020;VONGSRALUANG;BHATIASEVI, 2017), desempenho dos funcionários (GANDHI; SACHDEVA; GUPTA, 2018b, 2018a; GHANI; YASIN; ALI, 2019) e aplicações em restaurantes (KUKANJA; PLANINC, 2018PLANINC, , 2019. Além disso, percebeu-se a presença de aplicação de pesquisas em outras vertentes, como turismo (CARLSEN, 2011), lealdade dos consumidores (SARAPAIVANICH; PATTERSON, 2015), desenvolvimento de modelo baseado nos constructos da avaliação da qualidade de serviços (OWUSU-FRIMPONG; NWANKWO, 2012), cadeia de suprimentos (NAOUI, 2014) e relacionamento com fornecedores (GANDHI; SACHDEVA; GUPTA, 2019).…”
Section: Avaliação Da Qualidade De Serviço Em Pmesunclassified
“…De maneira geral, identificou-se que diversas pesquisas utilizaram diferentes ferramentas para a coleta de dados, como: entrevistas (CHEN; JAW; WU, 2016; NAOUI, 2014; OWUSU-FRIMPONG; NWANKWO, 2012), grupos focais com profissionais experientes na área para a validação dos modelos (AKMAN; DAGDEVIREN, 2018; GHOBAKHLOO; HONG; STANDING, 2015) e aplicação de questionários (KHAYER et al, 2020;SARAPAIVANICH;PATTERSON, 2015;SORKUN, 2019).…”
Section: Avaliação Da Qualidade De Serviço Em Pmesunclassified
See 1 more Smart Citation